The Effect of the Application of the Think Talk Write and Expository Learning Model on Learning Motivation and Learning Outcomes : Pengaruh Penerapan Model Pembelajaran Think Talk Write dan Expository terhadap Motivasi Belajar dan Hasil Belajar - Dzulifah Turnip, Melly; Djulia, Ely; Saragi, Daulat (JENIUS :Journal of Education Policy and Elementary Education Issues, 2025)
Improving student learning outcomes and motivation is a central focus in developing effective instructional models. This study compares the effects of the Think Talk Write (TTW) and Expository models on science learning outcomes, viewed from students' learning motivation levels. The research aims to: (1) determine the effect of learning motivation on science learning outcomes; (2) determine the effect of learning models (TTW and Expository) on science learning outcomes; and (3) examine the interaction between learning motivation and instructional models on students' science learning outcomes. Using a quantitative experimental design involving 64 students in Simalungun Regency, data were collected through tests and questionnaires and analyzed using Two-Way ANOVA. The analysis revealed that learning motivation significantly influenced outcomes (F = 3.188; p = 0.049; η² = 0.099), the learning model had a stronger effect (F = 11.587; p = 0.001; η² = 0.167), and there was a significant interaction between the model and motivation (F = 3.707; p = 0.031; η² = 0.113). The model accounted for 41.8% of the variance in learning outcomes (R² = 0.418). These findings highlight that aligning teaching models with students’ motivation levels especially through TTW enhances the effectiveness of science learning through active engagement and deeper conceptual understanding.